Role of (Na+)i and (Ca2+)i in nicotine-induced norepinephrine release from bovine adrenal chromaffin cells - Gerber, Stefan Horst; Haunstetter, Armin; Krüger, Carsten; Kaufmann, Alexander; Nobiling, Rainer; Haass, Markus (American journal of physiology. Cell physiology, 1995)
Intracellular free sodium ([Na+]i) and calcium ([Ca2+]i) concentrations were determined by sodium-binding benzofuran isophthalate (SBFI) and fura 2 microfluorimetry, respectively, in bovine adrenal chromaffin cells (BCC). Validation of SBFI microfluorimetry by in vitro and in vivo calibration revealed a reliable assessment of [Na+]i within a range of 1-30 mM in single BCC. Nicotine (0.1-10 microM) induced concentration-dependent increases of both [Na+]i (from 3.3 +/- 0.1 to 25.6 +/- 0.4 mM, n = 76, P < 0.001) and [Ca2+]i (from 64 +/- 1 to 467 +/- 16 nM, n = 87, P < 0.001), which were accompanied by an increase in [3H]norepinephrine (NE) release. Consistent with an exocytotic release mechanism, nicotine-induced increments of [Ca2+]i and [3H]NE release were reduced under calcium-free conditions and by gadolinium chloride (40 microM), whereas [Na+]i was not affected. In contrast, a parallel attenuation of nicotine-evoked changes in [Na+]i, [Ca2+]i, and [3H]NE release was observed during reduction of the extracellular sodium concentration. The nicotine-evoked responses were neutralized by the nicotinic receptor antagonist hexamethonium (100 microM) but not by blockade of voltage-dependent sodium channels (1 microM tetrodotoxin). In conclusion, the nicotine-induced exocytotic release of [3H]NE is triggered by an increase in [Ca2+]i, which is facilitated by sodium influx through the nicotinic receptor ionophore.
Gesehen am 12.05.2025